Complementary Food Hygiene Practice among Mothers or Caregivers in Bale Zone, Southeast Ethiopia: A Community Based Cross-Sectional Study - Shumi Bedada; Tomas Benti; Mekonnen Tegegne (Journal of Food Science and Hygiene, 2021)
Introduction Foodborne diseases are a major public health problem which predominantly affects infants and young children. Appropriate complementary food hygiene practice is very important to reduce the prevalence of foodborne illnesses. However, the information regarding this practice is not available and assessed before. Thus, the study was aimed to assess complementary food hygiene practices among mothers of children aged 6-23 months. Methods A community based cross-sectional study was conducted in Robe town on a samples of 517 mother-child pairs, which were selected by using systematic sampling technique. Data was collected using pre-tested and structured questionnaire, and each variable was described in the frequency and percentage. Bivariable and multivariable logistic regression analyses were used to identify factors associated with complementary food hygiene practice. Odds ratios with 95% confidence interval were used to assess levels of significance. Result The result indicated that 55% of participated mothers scored above the mean score of food hygiene practices. Mothers of children aged 12-23 months had higher odds to practice good food hygiene measures than those of aged 6-11 months (AOR, 1.82 95% CI (1.21, 2.73)). Mothers whose children attended growth monitoring session practice good food hygiene than their counterpart (AOR, 2.74 95% CI (1.49, 5.06)). Mothers having media exposure, and having knowledge on critical times of hand washing had relatively good food hygiene measures (AOR, 0.73 95 CI (1.14, 2.62)). Among food hygiene measures; handwashing with water and soap were low before eating food (17%), before feeding children (21%) and before preparing food (32%) when compared with after visiting the toilet (81%) and touching dirt (68%). Conclusion and Recommendation The study identified that food hygiene practices in the current study were mainly associated with child age, growth monitoring follow-up, maternal awareness about critical times of hand washing, and media exposure. So, improving knowledge of mothers on critical times of handwashing, strengthening growth monitoring follow-up and media promotion are important measures to improve food hygiene practices among mothers of infants and young children.
Keywords: Complementary food